Exploring the Intracrine Functions of VEGF-A - Wiszniak, Sophie (Biomolecules, 2021)
Vascular endothelial growth factor A (VEGF-A or VEGF) is a highly conserved secreted signalling protein best known for its roles in vascular development and angiogenesis. Many non-endothelial roles for VEGF are now established, with the discovery that VEGF and its receptors VEGFR1 and VEGFR2 are expressed in many non-vascular cell-types, as well as various cancers. In addition to secreted VEGF binding to its receptors in the extracellular space at the cell membrane (i.e., in a paracrine or autocrine mode), intracellularly localised VEGF is emerging as an important signalling molecule regulating cell growth, survival, and metabolism. This intracellular mode of signalling has been termed “intracrine”, and refers to the direct action of a signalling molecule within the cell without being secreted. In this review, we describe examples of intracrine VEGF signalling in regulating cell growth, differentiation and survival, both in normal cell homeostasis and development, as well as in cancer. We further discuss emerging evidence for the molecular mechanisms underpinning VEGF intracrine function, as well as the implications this intracellular mode of VEGF signalling may have for use and design of anti-VEGF cancer therapeutics.